Raising awareness of seizure triggers and pre-seizure behaviour changes in dogs. (2nd April 2020) - Packer, Rowena
Abstract : A new study by the Royal Veterinary College (RVC) has identified pre-seizure behavioural changes and potential seizure triggers that may help owners predict when a seizure is going to occur. The RVC's animal behaviour scientist Dr Rowena Packer explains.